Utilization of secondhand childcare products and perceived health risks among mothers of under-five years Children in Ibadan Metropolis, Nigeria. (2023)
Background: Second-hand economy is a universal phenomenon. In Nigeria, it cut across many decades and all spectrums of life even in childcare practice. The role of second-hand products in childcare practice and provisioning has been under reported in scholarly discuss in Nigeria. Hence, the prevalence of secondhand childcare products utilization, different categories of secondhand products available for childcare, the perceived health hazards and the reasons why consumers patronize secondhand products for childcare among mothers of under five years in Ibadan Nigeria. Methods: A cross-sectional concurrent mix-methods approach was used in the study. The quantitative and qualitative data were done simultaneously. While mothers of under-five children were purposively selected for in-depth interviews, a total sampling of all consenting mothers of under-five found at immunization clinic of Primary health care centres were sampled for survey. A total number of 403 mothers of under five children participated in the survey while 50 IDIs were conducted with buyers (mothers) and traders of secondhand children’s products. Qualitative data were subjected to thematic analysis, while the quantitative data were analyzed with descriptive statistics and chi-square test. Results: The mean age of mothers is } SD 28.6 } 5.4. Majority of respondents 209 (51.9%) had senior secondary education, 140 (34.7%) had tertiary education and only 2 (0.5%) had no formal education. About 339 (84.1%) utilized secondhand childcare products, while 64 (15.9%) never used secondhand childcare products. Mothers with at least senior secondary education 209 (51.9%) were found to be the highest users of secondhand childcare products. Procurement and utilization of secondhand childcare products was based on quality value, availability, affordability attached to constructed superiority of western civilization wrapped around provisioning in childcare. Conclusion: Many mothers of under-five children in Ibadan utilizes secondhand products in childcare. Embedding secondhand products health hazard in health talk during immunization clinics will be beneficial and help in educating mothers on reduced and safe utilization of secondhand products in childcare.